O POLSKIEJ POEZJI PO 1989 ROKU (BRAKI I „NADDATKI”) – SZKIC KRYTYCZNOLITERACKI - Kuczera-Chachulska, Bernadetta (Colloquia Litteraria, 2016)
The article addresses selected issues about Polish poetry after 1989. The author distinguishes between the poetry of ‘a literary movement’ and the poetry fulfilling the criteria of a veritable work of art. She critically com - ments on the selected works by well-known authors who function as part of an unspoken canon; she portrays the poetry of Paweł Marcinkiewicz as one of the most attractive proposals coming from the younger generation, whereas from among the classics she picks texts by Czesław Miłosz and Janusz St. Pasierb.